Integration of Physical, Genetic, and Cytogenetic Mapping Data for Cellulose Synthase (CesA) Genes in Flax (Linum usitatissimum L.) - Yurkevich, Olga Y.; Kirov, Ilya V.; Bolsheva, Nadezhda L.; Rachinskaya, Olga A.; Grushetskaya, Zoya E.; Zoschuk, Svyatoslav A.; Samatadze, Tatiana E.; Bogdanova, Marina V.; Lemesh, Valentina A.; Amosova, Alexandra V.; Muravenko, Olga V. (Frontiers in Plant Science, 2017)
Flax, L. usitatissimum L., is a valuable multi-purpose plant, and currently, its genome is being extensively investigated. Nevertheless, mapping of genes in flax genome is still remaining a challenging task. The cellulose synthase (CesA) multigene family involving in the process of cellulose synthesis is especially important for metabolism of this fiber crop. For the first time, FISH-based chromosomal localization of the CesA conserved fragment (KF011584.1), 5S and 26S rRNA genes was performed in landrace, oilseed and fiber varieties of L. usitatissimum. Intraspecific polymorphism in chromosomal distribution of KF011584.1 and 5S DNA loci was revealed, and the generalized chromosome ideogram was constructed. Using BLAST analysis, available data on physical/genetic mapping and also whole-genome sequencing of flax, localization of KF011584.1, 45S and 5S rRNA sequences on genomic scaffolds and their anchoring to the genetic map was conducted. The alignment of the results of FISH and BLAST analyses indicated that KF011584.1 fragment revealed on chromosome 3 could be anchored to linkage group 11. The common linkage group for 45S and 5S rDNA was not found probably due to the polymorphic localization of 5S rDNA on chromosome 1. Our findings indicate the complexity of integration of physical, genetic and cytogenetic mapping data for multicopy gene families in plants. Nevertheless, the obtained results can be useful for future progress in constructing of integrated physical/genetic/cytological maps in L. usitatissimum which are essential for flax breeding.